Paid sick days and stay-at-home behavior for influenza - Piper, Kaitlin; Youk, Ada; James, III, A. Everette; Kumar, Supriya (PLOS ONE, 2017)
Access to paid sick days (PSD) differs by workplace size, race/ethnicity, gender, and income in the United States. It is not known to what extent decisions to stay home from work when sick with infectious illnesses such as influenza depend on PSD access, and whether access impacts certain demographic groups more than others. We examined demographic and workplace characteristics (including access to PSD) associated with employees’ decisions to stay home from work for their own or a child’s illness. Linking the 2009 Medical Expenditure Panel Survey (MEPS) consolidated data file to the medical conditions file, we used multivariate Poisson regression models with robust variance estimates to identify factors associated with missed work for an employee’s own or a child’s illness/injury, influenza-like-illness (ILI), and influenza. Controlling for gender, race/ethnicity, education, and income, access to PSD was associated with a higher probability of staying home for an employee’s own illness/injury, ILI, or influenza, and for a child’s illness/injury. Hispanic ethnicity was associated with a lower prevalence of staying home for the employee’s own or a child’s illness compared to non-Hispanic Whites. Access to PSD was associated with a significantly greater increase in the probability of staying home among Hispanics than among non-Hispanic Whites. Women had a significantly higher probability of staying home for their child’s illness compared to men, suggesting that women remain the primary caregivers for ill children. Our results indicate that PSD access is important to encourage employees to stay home from work when sick with ILI or influenza. Also, PSD access may be important to enable stay-at-home behavior among Hispanics. We conclude that access to PSD is likely to reduce the spread of disease in workplaces by increasing the rate at which sick employees stay home from work, and reduce the economic burden of staying home on minorities, women, and families.